Difficult airway management in an emergency in Nepal - Das, Sunil Kumar; Mahato, Gaurav (Journal of General Practice and Emergency Medicine of Nepal, 2022)
Introduction: Health care provider often face challenges in managing airway in-patients in emergency department having respiratory compromise. Here in this review, we have discussed advances in management of difficult airway in emergency setting in Nepal. Method: Articles available in google scholar with key word “airway management,’’ “difficult airway,” “emergency,” “failed intubation,” “Nepal” were retrieved. Amongst which 14 articles were retrieved for the discussion. Result: MMT was better for predicting difficult laryngoscopy when compared to measurement of sternomental, thyromental and inter-incisor distances and grading of mandibular protrusion. Similarly, when comparing upper lip bite test to MMT, ULBT has better sensitivity and specificity. Laryngoscopic view with 5 cm of head elevation had a better visualization. Conclusion: The available evidence recommends using upper lip bite test in emergency setting with comparison to modified / mallampati classification. Different tests can be used in accordance to urgency of intervention. Similarly, head elevation of 5 cm can be routinely practiced for better visualization during laryngoscopy.